2019
DOI: 10.1097/01.hs9.0000564760.61745.ba
|View full text |Cite
|
Sign up to set email alerts
|

S1628 Targeting the Immunophilin Fkbp12 by Drug Repurposing or Rnase‐based Approaches for Bmp‐smad Pathway and Hepcidin Upregulation in Hereditary Hemochromatosis

Abstract: Results: 155 patients underwent allogeneic HCT for AML at our institution during the study period. Disease status was defined as CR in 80 (52%), CRi in 55 (35%) and AD in 20 (13%). There were no significant demographic or transplant characteristics between the groups. The 5-year probability of survival for CR patients was 51.3% (95%CI 40.2-65.4), compared to 24.4% (95%CI 14.1-42.4) for CRi and 12.7% (95%CI 3.6-45.2) for AD (p<0.001) (adjusted HR 1.92 (95% CI 1.20-3.06, p = 0.006) for CRi and 2.82 (95% CI 1.39-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dr Silvestri recently investigated the molecular mechanism underlying FKBP12 regulation of BMP-SMAD pathway activation and hepcidin expression. 9 Through pharmacologic and genetic studies, FKBP12 was shown to modulate BMP-receptor interactions and ligand sensitivity. Mechanistically, BMP6 and TAC increase ALK2 homo- and ALK2-ALK3 hetero-oligomerization and the interaction between ALK2 and the type II receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dr Silvestri recently investigated the molecular mechanism underlying FKBP12 regulation of BMP-SMAD pathway activation and hepcidin expression. 9 Through pharmacologic and genetic studies, FKBP12 was shown to modulate BMP-receptor interactions and ligand sensitivity. Mechanistically, BMP6 and TAC increase ALK2 homo- and ALK2-ALK3 hetero-oligomerization and the interaction between ALK2 and the type II receptors.…”
mentioning
confidence: 99%
“…Both the physiological ALK2 ligand BMP6 and the immunosuppressive drug Tacrolimus (TAC) displace FKBP12 from ALK2 and activate signal transduction. Dr Silvestri recently investigated the molecular mechanism underlying FKBP12 regulation of BMP‐SMAD pathway activation and hepcidin expression 9 . Through pharmacologic and genetic studies, FKBP12 was shown to modulate BMP‐receptor interactions and ligand sensitivity.…”
mentioning
confidence: 99%